Altruistic Economic Character of High School Students in Daily Alms Practice: Conceptual Study of the Integration of Positive Psychology and Maqasid Syariah - Zulkifli Sumantri (Publikasi Indonesia, 2025)
This study aims to develop a conceptual model of Islamic economic character education based on the integration of positive psychology and maqasid al-shariah theories. The main problem addressed concerns how PERMA, PROSPER, PRIMED, and maqasid al-shariah can be integrated into a comprehensive character education system to cultivate a morally conscious economic character through daily charity activities in secondary schools. A conceptual literature study was conducted using thematic analysis guided by Creswell and qualitative data analysis techniques from Miles, Huberman, and Saldaña. The analysis resulted in the integrative P3M model (PERMA–PROSPER–PRIMED–Maqasid) that explains the mechanism for developing spiritual-social economic character, referred to as the Altruistic Flourishing Economic Character . This model represents a theoretical novelty by bridging Western perspectives on psychological well-being with Islamic ethics of public good. The study contributes to strengthening economic character education in schools and supports the achievement of SDG 4 (quality education) and SDG 12 (responsible consumption and production).